Construction of industrial process models: innovation in the teaching-learning process (Research, Society and Development, 2020)
This article aims to present the possibility of a creative learning strategy for classes in the Industrial Processes discipline of the Environmental Engineering Course at UEMG. This discipline is seen by many students as difficult to understand, since it addresses the teaching of processes and the knowledge of equipment, in addition to calculations involving sizing, although simple, but which are not routine in Higher Education. Thus, an alternative for a better understanding of the contents of this discipline was the realization of a “Model Exhibition to illustrate Industrial Processes” and aimed to provide an approach to the contents taught in class, in a more dynamic way, facilitating the teaching-learning process. In this event, the students, using their creativity, should make models to illustrate an industrial process chosen by the group. This work made it possible for undergraduates to learn about the development of industrial processes, in addition to allowing familiarization and identification of the various unit operations involved in technological processes of a manufacturing nature. Still, the activities provided an understanding of technological issues, arousing the curiosity of teachers, students and visitors from different areas.